1999
DOI: 10.1071/ea98067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pollen donors for the sweet cherry cultivars ‘Stella’ and ‘Summit’ by isozyme analysis

Abstract: Pollinisers of the sweet cherry cultivars ‘Stella’ and ‘Summit’ were determined by analysing isozymes of glucose-6-phosphate dehydrogenase (G6PD), 6-phosphogluconate dehydrogenase (6-PGD), glucose phosphate isomerase (GPI), isocitrate dehydrogenase (IDH), shikimate dehydrogenase (SKDH), fructose-1,6-diphosphatase (FDP), and glutamate oxaloacetate transaminase (GOT) in their embryos. Possible polliniser cultivars were selected on the basis of similar full bloom dates and orchard position in regard to Stella or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…† Recombination frequency cannot be estimated because pollen donor is homozygous at the SSR locus. planting design and mixture of cultivars (Brant et al 1999). For example, in open-pollinated breeding populations, new advantageous combinations may be identified without performing laborious controlled crosses.…”
mentioning
confidence: 99%
“…† Recombination frequency cannot be estimated because pollen donor is homozygous at the SSR locus. planting design and mixture of cultivars (Brant et al 1999). For example, in open-pollinated breeding populations, new advantageous combinations may be identified without performing laborious controlled crosses.…”
mentioning
confidence: 99%
“…Granger (1997) found that the selfcompatible cultivar Stella outcrossed in 70% of successful pollinations and selfed in 30%, and concluded that it was necessary to include polliniser cultivars in plantings of self-compatibles; this finding concurs with the results for Sunburst which add further support to this conclusion. Brandt et al (1999) found Stella to be the main polliniser for Summit; in this study, Stella contributed about 30% of pollen genes to Summit embryos, while Van and Merchant made larger contributions. Jackson and Clarke (1991) found that gene flow in almond orchards was concentrated between neighbouring parts of tree canopies and no gene flow occurred beyond 76 m. In comparison, Granger (1997) found that 50% of gene flow in a cherry orchard occurred over 50 m. In this study the main polliniser was usually within approximately 20 m.…”
Section: Discussionmentioning
confidence: 80%